Physiological Responses of Two Moss Species to the Combined Stress of Water Deficit and Elevated Nitrogen Deposition. I. Secondary Metabolism - Liu, Bin-yang; Lei, Chun-yi; Jin, Jian-hua; Li, Shan; Zhang, Yi-shun; Liu, Wei-qiu (International journal of plant sciences, 2015)
Premise of research. It has been well documented that secondary metabolites in mosses can protect mosses from pathogen or herbivore attacks, but their functions in abiotic stress are poorly understood. Thus, we have investigated effects of water deficit and high nitrogen (N) on secondary metabolism in two moss species. Methodology. KNO3 or NH4Cl was supplied to Pogonatum cirratum subsp. fuscatum and Hypnum plumaeforme at rates of 20–60 kg N hm−2 for 1 yr, water was then withheld for 12 d, and finally a 10-d recovery treatment was applied. Indexes of oxidative stress (superoxide dismutase [SOD], malondialdehyde [MDA]) and secondary metabolism were determined after the water-withholding and recovery treatments, respectively. Pivotal results. Both ammonium and nitrate supply stimulated SOD activity and MDA accumulation as well as the synthesis of phenylpropanoids, triterpenes, and total alkaloids. Water-deficit stress induced oxidative stress in both moss species, and N application exacerbated the oxidative stress. Water deficit inhibited SOD and L-phenylalanine ammonia-lyase activities and changed their phenylpropanoid profiles (with interspecific differences). Triterpene accumulation was stimulated by water deficit in H. plumaeforme (but not in P. cirratum), while alkaloid accumulation was stimulated in both mosses. After the 10-d recovery period, the N treatments generally still had significant effects on SOD activity and secondary metabolite contents, and water deficit still had effects on contents of some phenolics and alkaloids. However, SOD activity in the water-deficit-treated P. cirratum samples was restored after recovery, indicating that it may play an important role in recovery from stress induced by water deficit. Conclusions. The secondary metabolism of both mosses is intimately linked to their antioxidant mechanisms. Phenylpropanoids, triterpenes, and alkaloids may mark moss responses to stress and therefore present a useful method for environmental monitoring in the mosses.